A Look at the Indo-European Arch Rhythmics (a comparative analysis of the musical rhythmics of Hindus, Arabs, Greeks, and Balts) - Velička, Eirimas (Acta Orientalia Vilnensia, 2003)
This article analyzes and compares the rhythmics of Indian, Arabian, ancient Greek, ethnic Lithuanian, Latvian, and Estonian music. The stress is laid on the similarity common to classical Indian, ancient Greek, and ethnic Lithuanian music. The author poses the question: can the durational rhythmics, which is common among the mentioned cultures, be called “Indo-European Arch rhythmics”; or is it a phenomenon of a wider scale, typical in the music of other cultures, too. The research is based on typological and comparative methods. The phenomenon of musical rhythmics is analyzed following the quantitative (duration, quantity) view. The foundation of quantitative (durational) rhythmics is sought for in languages as well- in the fluctuation of long and short syllables.